Estudo químico de plantas com atividades sobre insetos sociais - Almeida, Sheylla Susan Moreira da Silva de (Universidade Federal de São Carlos, 2007)
The chemical control of pest, which uses conventional insecticides, shows a number of advantages to agriculturists due to its efficiency, lower cost and facility of use in related to others. However, the utilization of the chemical control with nonselective insecticides, without culture rotation, could cause instability eliminating beneficial insects, increasing populations of pests, and mainly loosing insecticide efficacy due to natural selection from insects resistant to these chemicals. Besides that, there are more negative aspects referring to environmental contamination, such soil, water, atmosphere and others organisms contaminations, and accidental damage caused by bad utilization of insecticides. The investigation for substances with insecticide activity from plants aims the insect control and lower environmental impact. Based on agriculturist information about plants utilized for leaf-cutting ant control, field observations and chemosystematic data from the literature, the Natural Products Group from the Chemistry Department of São Carlos Federal University together the Study Center of Social Insects of UNESP in Rio Claro have been studied the effects of plants potentially toxic to those ants. The fall disease , as it is known by beekeepers, consists in death of Apis mellifera in autumn and it is caused by toxic compounds, which are carried to beehives with nectar, has also been studied by this team. This work describes the chemical study of Dimorphandra mollis, Sthyphnodendro adstringens and Helietta puberula associated to their actions in ants and bees. The toxicity study in model fish aims to evaluate the impact that several substances with insecticide activity could cause to the environment. The phytochemical study, besides the search for secondary metabolic, aimed to contribute to chemosystematic of vegetal species. It was employed traditional chromatographic techniques and even on-line ones such as GC-MS and LC-UV-MS to obtain compounds from the plants studied and also to chemistry identification, associated with NMN spectroscopic experiments. From extracts fractionation were obtained several compounds of various classes such as alcohols (S17), fatty acids (S18 S43, S52 S62, S89 S95), hydrocarbons (S4 S16), cinnamic acid derivative (S47, S48, S50, S51, S63 e S64), glycosides (S65 S67), steroids (S44 - S46, S96 - S99), triterpenes (S100), flavonoids (S1 S3, S68 S88, S100 S105) and alkaloids (S49). The extracts from the vegetable species studied showed insecticide activity against at least one tested model. The flavonoids astilbin, isoastilbin and catechin, obtained from D. mollis, were tested in model fish and they did not show toxic activity, therefore they could be promising for the use in plantations near aquatic environments since they will not damage these ecosystems. Once identified and isolated the compounds with insecticide activity from plants with potential utilization in the production of natural products, it is expected a reduction in the environmental ecosystems impact caused by synthetic insecticides. It is possible to note that the development of prospecting research and evaluation of plants with insecticide activity have great economic importance, as well as for environmental conservation of agroecosystems where the active fractions from these plants could be utilized as natural insecticides in pest integrated management.
Chemical investigation of active plants against social insects
Keywords: Produtos naturais; Formiga; Abelha; Inseticidas vegetais; CIENCIAS EXATAS E DA TERRA::QUIMICA